Anti-Osteoporotic Mechanisms of Polyphenols Elucidated Based on In Vivo Studies Using Ovariectomized Animals - Yoshimi Niwano; Hidetsugu Kohzaki; Midori Shirato; Shunichi Shishido; Keisuke Nakamura (MDPI AG, 2022)
Polyphenols are widely known for their antioxidant activity, i.e., they have the ability to suppress oxidative stress, and this behavior is mediated by the autoxidation of their phenolic hydroxyl groups. Postmenopausal osteoporosis is a common health problem that is associated with estrogen deficiency. Since oxidative stress is thought to play a key role in the onset and progression of osteoporosis, it is expected that polyphenols can serve as a safe and suitable treatment in this regard. Therefore, in this review, we aimed to elucidate the anti-osteoporotic mechanisms of polyphenols reported by in vivo studies involving the use of ovariectomized animals. We categorized the polyphenols as resveratrol, purified polyphenols other than resveratrol, or polyphenol-rich substances or extracts. Literature data indicated that resveratrol activates sirtuin 1, and thereafter, suppresses osteoclastogenic pathways, such as the receptor activator of the nuclear factor kappa B (RANK) ligand (RANKL) pathway, and promotes osteoblastogenic pathways, such as the wingless-related MMTV integration site pathway. Further, we noted that purified polyphenols and polyphenol-rich substances or extracts exert anti-inflammatory and/or antioxidative effects, which inhibit RANKL/RANK binding via the NF-κB pathway, resulting in the suppression of osteoclastogenesis. In conclusion, antioxidative and anti-inflammatory polyphenols, including resveratrol, can be safe and effective for the treatment of postmenopausal osteoporosis based on their ability to regulate the imbalance between bone formation and resorption.